Short communication: use of the output video signal for dynamic range, brightness control and image memory assessment in X-ray fluoroscopy - Okkalides, D (British journal of radiology, 1996)
The output video signal from three X-ray fluoroscopy machines was recorded with a storage oscilloscope to calculate the dynamic range of their image intensifier television camera chains. The two MERATE MTH90 and MGR50hf machines employed the same imaging chain but the response of the former to exposure was significantly lower because of a three channel light distribution optical system which was installed but not used. The CGR Stenoscope machine was found to have a very narrow dynamic range to the extent that it was not usable. Additional measurements on the CGR machine showed that the image intensifier brightness control mechanism would produce stabilized brightness in less than 0.4 s and it proved to be faster than the manual selection of exposure parameters. The quality of the image stored in the memory device on the same system was compared with the original by subtracting the two video signals on the oscilloscope and thus acquiring a quantitative measure of their difference.